2022
DOI: 10.1002/arch.21886
|View full text |Cite
|
Sign up to set email alerts
|

Map‐based cloning and functional analysis revealed ABCC2 is responsible for Cry1Ac toxin resistance inBombyx mori

Abstract: Bt toxins are parasporal crystals produced by Bacillus thuringiensis (Bt). They have specific killing activity against various insects and have been widely used to control agricultural pests. However, their widespread use has developed the resistance of many target insects. To maintain the sustainable use of Bt products, the resistance mechanism of insects to Bt toxins must be fully clarified. In this study, Bt-resistant and Bt-susceptible silkworm strains were used to construct genetic populations, and the ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 52 publications
(67 reference statements)
0
1
0
Order By: Relevance
“…The common response of P. massoniana included the ABC transporter, arginine, and proline pathways. First, ABC transporters were involved in the transport of secondary metabolites and plant hormones, detoxification, and signal transduction, which indirectly aided resistance to PWN (Wang et al, 2022; Li et al, 2024; Zhou et al, 2024). Second, arginine and proline indirectly affected the reproduction and pathogenicity of the PWN by promoting plant growth and development, enhancing stress resistance, acting as antioxidant defense molecules, participating in defense responses, and regulating metabolic pathways (Zhang et al, 2022; Theisen et al, 2024; Wang et al, 2024b).…”
Section: Discussionmentioning
confidence: 99%
“…The common response of P. massoniana included the ABC transporter, arginine, and proline pathways. First, ABC transporters were involved in the transport of secondary metabolites and plant hormones, detoxification, and signal transduction, which indirectly aided resistance to PWN (Wang et al, 2022; Li et al, 2024; Zhou et al, 2024). Second, arginine and proline indirectly affected the reproduction and pathogenicity of the PWN by promoting plant growth and development, enhancing stress resistance, acting as antioxidant defense molecules, participating in defense responses, and regulating metabolic pathways (Zhang et al, 2022; Theisen et al, 2024; Wang et al, 2024b).…”
Section: Discussionmentioning
confidence: 99%
“…The ABC transporter belongs to a family of membrane proteins [22], and animal members of the ABC family were first found in the human genome [23], and, subsequently, in all animals [24]. In insects, including Bombyx mori, midgut ABC transporters play a role in uric acid metabolism and resistance to insecticides [25][26][27][28], and studies have shown that the ABC transporter specific to the silkworm midgut is related to the response of silkworm molting hormone responses (20-E) [29]. In silkworms of the same sex, the midgut metabolites in individuals fed on an AD and ML were enriched in the ABC transporter signaling pathway and no differences between the sexes were observed, while the intestinal metabolites of silkworms fed on the same diet showed no ABC transporter enrichment (Supplementary Figure S4).…”
Section: Discussionmentioning
confidence: 99%